Respuesta :

Answer: 6

Step-by-Step Explanation:

We first Solve for ‘x’ :-

=> 5(3x - 1) = 55
= 15x - 5 = 55
= 15x = 55 + 5 = 60
=> x = 60/15 = 4

Therefore, x = 4

We can now Substitute the value of ‘x’ in 2x - 2 to find the value :-

= 2x - 2
= 2(4) - 2
= 8 - 2
= 6

Therefore, 2x - 2 = 6 (as x = 4)

Hey ! there

Answer:

  • Value of 2x - 2 is 6 .

Step-by-step explanation:

In this question we are provided with an equation that is 5 ( 3x - 1 ) = 55 and we are asked to find the value of 2x - 2 .

Firstly , we need to find the value of x . So we need to solve the equation .

SOLUTION : -

[tex] \quad \longmapsto \qquad \: 5(3x - 1) = 55[/tex]

Step 1 : Dividing with 5 on both sides :

[tex] \quad \longmapsto \qquad \: \dfrac{ \cancel{5}(3x - 1)}{ \cancel{5}} = \cancel{\dfrac{55}{5} }[/tex]

On cancelling , We get :

[tex] \quad \longmapsto \qquad \:3x - 1 = 11[/tex]

Step 2 : Adding 1 on both sides :

[tex] \quad \longmapsto \qquad \:3x - \cancel{1} + \cancel{1} = 11 + 1[/tex]

On simplifying , We get :

[tex] \quad \longmapsto \qquad \:3x = 12[/tex]

Step 3 : Dividing with 3 on both sides :

[tex] \quad \longmapsto \qquad \: \dfrac{ \cancel{3}x}{ \cancel{3}} = \cancel{ \dfrac{12}{3} }[/tex]

We get ,

[tex] \quad \longmapsto \qquad \: \underline{\boxed{\frak{x = 4}}}[/tex]

→ Therefore , value of x is 4 .

Verifying : -

Now we are verifying whether our answer is wrong or right . So ,

  • 5 ( 3x - 1 ) = 55

  • 5 { 3( 4 ) - 1 } = 55

  • 5 ( 12 - 1 ) = 55

  • 5 ( 11 ) = 55

  • L.H.S = R.H.S

  • Hence , Verified .

Therefore , our value of x is correct/valid .

We need to find the value of 2x - 2 .

[tex] \quad \longmapsto \qquad \:2x - 2[/tex]

So substituting value of x in it :

[tex]\quad \longmapsto \qquad \:2( \bold{4}) - 2[/tex]

Multiplying 2 with 4 :

[tex]\quad \longmapsto \qquad \:8 - 2[/tex]

Subtracting 2 from 8 :

[tex]\quad \longmapsto \qquad \: \blue{\underline{\boxed{\frak{6}}}} \quad \: \bigstar[/tex]

  • Henceforth, value of 2x - 2 is 6 .

#Keep Learning

ACCESS MORE